2021
DOI: 10.1177/08912432211046982
|View full text |Cite
|
Sign up to set email alerts
|

A Patchwork of Femininities: Working-Class Women’s Fluctuating Gender Performances in a Pakistani Market

Abstract: Scholars have studied multiple femininities across different spaces by attributing variation to cultural/spatial contexts. They have studied multiple femininities in the same space by attributing variation to class/race positions. However, we do not yet know how women from the same cultural, class, and race locations may enact multiple femininities in the same context. Drawing on observations and interviews in a women-only bazaar in Pakistan, I show that multiple femininities can exist within the same space an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…For example, in a study conducted by Siles et al (2022), it was observed that participants attributed political valences to TikTok recommendations, specifically linking them to a presidential candidate from Costa Rica based on the interests of users "with the same profile" (p. 12). Another example is Kamran's (2023) recent study on Pakistani TikTok users, where the author observes that the presence on TikTok is often associated with a "low-class femininity" (p. 1) in Pakistani society. Algorithms play a significant role in how users search for information and, simultaneously, in how knowledge systems are embodied through algorithms (Gillespie, 2014).…”
Section: Institutional Legitimation As a Form Of Agency Negotiationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study conducted by Siles et al (2022), it was observed that participants attributed political valences to TikTok recommendations, specifically linking them to a presidential candidate from Costa Rica based on the interests of users "with the same profile" (p. 12). Another example is Kamran's (2023) recent study on Pakistani TikTok users, where the author observes that the presence on TikTok is often associated with a "low-class femininity" (p. 1) in Pakistani society. Algorithms play a significant role in how users search for information and, simultaneously, in how knowledge systems are embodied through algorithms (Gillespie, 2014).…”
Section: Institutional Legitimation As a Form Of Agency Negotiationmentioning
confidence: 99%
“…However, this restricted scope can be advantageous as it validates the institutional elements unique to Romania. Further studies could investigate the complex interplay between the algorithmic stories and the institutional values in other cultural contexts, given the fact that research has been carried out on TikTok activity in Costa Rica (Siles et al, 2022), Pakistan (Kamran, 2023), and so on. Another limitation arises from the relatively short distance between the stages of this study.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%
“…Nation-building requires valorizing a specific vision of womanhood and regulating any threats to this vision (Jamal, 2006). In Pakistan, ideal womanhood is predicated on gender seclusion, sexual modesty, respectability, middle-classness, domesticity, and distance from the public sphere (Kamran, 2021;Khoja-Moolji, 2018). Bans on TikTok in Pakistan are thus a continuation of a long history of state formation through repression of women's agency and sexuality (Toor, 2007) and other non-normative displays of gender and sexuality.…”
Section: Gender Transgressions Moral Panics and The Digital Public Sp...mentioning
confidence: 99%
“…Embodied performances of daily life are forms of discourse enabling resistance to manifest (Butler, 2002). Women are not passive embodiments of femininity or motherhood, but rather involved in active, strategic production of alternative approaches, piecing together different performances of both femininity and maternity to enable survival for themselves and their children (Cruikshank, 1999;Skeggs, 2004;McCormack, 2005;Kamran, 2021). Laws, policy, and media discourse are strategies through which ontological legitimacy is gained, and which then generate logical and reasonable courses of action (Foucault, 1980).…”
Section: Introductionmentioning
confidence: 99%